2008
DOI: 10.1073/pnas.0806585105
|View full text |Cite
|
Sign up to set email alerts
|

Beyond tumor necrosis factor receptor: TRADD signaling in toll-like receptors

Abstract: Tumor necrosis factor receptor 1-associated death domain protein (TRADD) is the core adaptor recruited to TNF receptor 1 (TNFR1) upon TNF␣ stimulation. In cells from TRADD-deficient mice, TNF␣-mediated apoptosis and TNF␣-stimulated NF-B, JNK, and ERK activation are defective. TRADD is also important for germinal center formation, DR3-mediated costimulation of T cells, and TNF␣-mediated inflammatory responses in vivo. TRADD deficiency does not enhance IFN␥-induced signaling. Importantly, TRADD has a novel role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 27 publications
3
90
0
1
Order By: Relevance
“…Because it has a strong affinity for RIP1, TRADD enables the efficient recruitment RIP1 to the TNFR1 receptor complex (Ermolaeva et al, 2008;Pobezinskaya et al, 2008). However, in the absence of TRADD, RIP1 maintains a weak interaction with TNFR1, suggesting that there is also a direct interaction between 653 RIP1 attenuates noncanonical NF-B RIP1 and TNFR1 (Chen et al, 2008;Ermolaeva et al, 2008;Pobezinskaya et al, 2008). Our data here show that loss of this interaction (through a RIP1 deficiency) permits greater TRADD recruitment to TNFR1.…”
Section: Discussionmentioning
confidence: 65%
“…Because it has a strong affinity for RIP1, TRADD enables the efficient recruitment RIP1 to the TNFR1 receptor complex (Ermolaeva et al, 2008;Pobezinskaya et al, 2008). However, in the absence of TRADD, RIP1 maintains a weak interaction with TNFR1, suggesting that there is also a direct interaction between 653 RIP1 attenuates noncanonical NF-B RIP1 and TNFR1 (Chen et al, 2008;Ermolaeva et al, 2008;Pobezinskaya et al, 2008). Our data here show that loss of this interaction (through a RIP1 deficiency) permits greater TRADD recruitment to TNFR1.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, we found that MC159 enhanced the binding between RIP1 and TRADD, two essential adaptors for NF-B activation, by multiple TLRs and TNF receptors (9,17,38). We propose that enhanced interaction between RIP1 and TRADD might underlie the mechanism by which MC159 promotes NF-B signaling by innate immune receptors.…”
Section: Discussionmentioning
confidence: 81%
“…5A, compare panels b and d). The adaptor proteins TRADD (9,17,38) for multiple receptors, including TNF receptor 1 (TNFR-1) and TLR4. We therefore tested whether MC159 might enhance NF-B activation through TRADD and RIP1.…”
Section: Mc159 Transgenic Mice Exhibited Enhanced Control Of Vv Infecmentioning
confidence: 99%
“…This mechanism of Complex-I assembly is well established for some cell types, and the molecular interactions between TRADD, TRAF2, and cIAPs have been revealed by crystallography, as depicted schematically in Figure 6. It is worth remarking, however, that neither TRADD nor RIPK1 are essential components for Complex-I-mediated activation of NF-kB in all cells (Chen et al 2008;Ermolaeva et al 2008;Pobezinskaya et al 2008;Wong et al 2010). In stark contrast, cIAPs are indispensable for TNF-induced activation of NF-kB in all cell types tested so far Varfolomeev et al 2008;Haas et al 2009).…”
Section: Iap-mediated Regulation Of Innate Immunity and Cell Survivalmentioning
confidence: 94%